Levels of early-childhood behavioral inhibition predict distinct neurodevelopmental pathways to pediatric anxiety. Issue 1 (8th January 2019) - Abend, Rany; Swetlitz, Caroline; White, Lauren K.; Shechner, Tomer; Bar-Haim, Yair; Filippi, Courtney; Kircanski, Katharina; Haller, Simone P.; Benson, Brenda E.; Chen, Gang; Leibenluft, Ellen; Fox, Nathan A.; et al.
Abstract: Background: Anxiety symptoms gradually emerge during childhood and adolescence. Individual differences in behavioral inhibition (BI), an early-childhood temperament, may shape developmental paths through which these symptoms arise. Cross-sectional research suggests that level of early-childhood BI moderates associations between later anxiety symptoms and threat-related amygdala–prefrontal cortex (PFC) circuitry function. However, no study has characterized these associations longitudinally. Here, we tested whether level of early-childhood BI predicts distinct evolving associations between amygdala–PFC function and anxiety symptoms across development. Methods: Eighty-seven children previously assessed for BI level in early childhood provided data at ages 10 and/or 13 years, consisting of assessments of anxiety and an fMRI-based dot-probe task (including threat, happy, and neutral stimuli). Using linear-mixed-effects models, we investigated longitudinal changes in associations between anxiety symptoms and threat-related amygdala–PFC connectivity, as a function of early-childhood BI. Results: In children with a history of high early-childhood BI, anxiety symptoms became, with age, more negatively associated with right amygdala–left dorsolateral-PFC connectivity when attention was to be maintained on threat. In contrast, with age, low-BI children showed an increasingly positive anxiety–connectivity association during the same task condition. Behaviorally, at age 10, anxiety symptoms did not relate to fluctuations in attention bias (attention bias variability, ABV) in either group; by age 13, low-BI children showed a negative anxiety–ABV association, whereas high-BI children showed a positive anxiety–ABV association. Conclusions: Early-childhood BI levels predict distinct neurodevelopmental pathways to pediatric anxiety symptoms. These pathways involve distinct relations among brain function, behavior, and anxiety symptoms, which may inform diagnosis and treatment.